Assessing and addressing groundwater depletion in yemen’s Ibb sub-basins: an original study on challenges and sustainable management strategies - Yahia Alwathaf; Nabil Al-Areeq; Ahmed M. Al-Areeq; Fatma Aksever (All Earth)
The United Nations’ Sustainable Development Goal 6 underscores the need for accessible and sustainable water management, a challenge particularly acute in Yemen’s Ibb sub-basins due to severe groundwater overexploitation. While previous studies have examined water scarcity, this study introduces an innovative approach by integrating scenario-based projections and empirical groundwater recharge modelling with a comprehensive management strategy. This research bridges critical knowledge gaps and offers a replicable framework for sustainable water management in arid regions. The current groundwater withdrawal trends and their long-term impacts were investigated to propose a multi-faceted management strategy for the study area. The finding showed that the recharge rates is less than the groundwater withdrawal with a deficit of −10 mm3 in 2021 and could increase to −44 mm3 in 2040. However, it is expected that the aquifers will be depleted by 2029 if no intervention is taken. As a result, interventions such as dam rehabilitation, rainwater harvesting, efficient irrigation methods, and wastewater reuse were proposed which could save 47 mm3 annually by 2040. These findings stress the urgency of implementing integrated water resource management strategies to avert crises and ensure groundwater sustainability, serving as a model for arid regions globally.